Effect of Pore Size on Cell Behavior Using Melt Electrowritten Scaffolds - Han, Yu; Lian, Meifei; Wu, Qiang; Qiao, Zhiguang; Sun, Binbin; Dai, Kerong (Frontiers in Bioengineering and Biotechnology, 2021)
Tissue engineering technology has made major advances with respect to the repair of injured tissues, for which scaffolds and cells are key factors. However, there are still some issues with respect to the relationship between scaffold and cell growth parameters, especially that between the pore size and cells. In this study, we prepared scaffolds with different pore sizes by melt electrowritten (MEW) and used mesenchymal stem cells (BMSCs), chondrocytes (CCs), and tendon stem cells (TCs) to study the effect of the scaffold pore size on cell adhesion, proliferation, and differentiation. It was evident that different cells demonstrated different adhesion and proliferation rates on the scaffold. Further, different cell types showed differential preferences for scaffold pore sizes, as evidenced by variations in cell viability. The pore size also affected the differentiation and gene expression pattern of cells. Among the tested cells, BMSCs exhibited the greatest viability on the 200 μm pore size scaffold, CCs on the 200 μm and 100 μm, and TCs on the 300 μm scaffold. The scaffolds with the 100 μm and 200 μm pore sizes induced significantly higher proliferation, chondrogenic gene expression, and cartilage-like matrix deposition after in vitro culture, relative to scaffolds with smaller or large pore sizes (especially 50 μm and 400 μm). Taken together, these results show that the micro-architecture of tissue engineering scaffolds for different tissues should be different, and that the pore size is critical for the development of advanced tissue engineering strategies for tissue repair.